DESCRIPTION STUDY OF QUALITY MANAGEMENT IMPLEMENTATION OF ISO 9001:2015 HANDLING OF FLIGHT DELAYS AT AIRASIA - Siti Roheti; Kuncorosidi Kuncorosidi (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2020)
The implementation of ISO 9001: 2015 quality management is a real effort made by PT Indonesia AirAsia to provide the best service to passengers, in practice AirAsia runs this system in accordance with the regulation of the Minister of air transportation number 89 of 2015 which is about handling flight delays, in addition to passengers who experiencing delays must also be compensated by AirAsia. This study aims to determine the implementation of ISO 9001: 2015 quality management at AirAsia. In this research the method used is descriptive, the type of data in this study is secondary data, and data collection techniques are done by observation, literature study, journals related to ISO quality management, articles related to the implementation of ISO 9001: 2015 quality management. The results of this study reveal that AirAsia has implemented an ISO 9001: 2015 management system in handling late services. The objectives and benefits of implementing ISO 9001: 2015 quality management are: 1) to increase AirAsia passenger confidence in AirAsia quality 2) provide AirAsia quality assurance 3) increase company productivity 4) increase employee motivation 5) establish mutually beneficial relationships with suppliers 6) achieve savings optimum costs 7) identify risks and opportunities in improving service quality.